Molecular devices based on reversible singlet oxygen binding in optical and photomedical applications. - SENGE, MATHIAS (My University, 2016)
Polycyclic aromatic hydrocarbons are known to bind singlet oxygen with formation of endoperoxides, which can be released upon heating. This process is now capturing broad attention due to its potential in photomedicine. Singlet oxygen generation upon decomposition of endoperoxides at ambient temperatures represents an alternative to classical photodynamic therapy (PDT), which is limited by hypoxia and reduced light penetration into cancer tissue. Moreover, endoperoxide formation with chromophoric molecules allows for a straightforward modification of the optical properties of the photoactive materials, e.g., shifting of the absorption/emission wavelength which is usually achieved by chemical tuning. This review provides a summary of the latest advances in this area of research along with a discussion of the basic properties of organic endoperoxides.
PUBLISHED